A Communicative - Functional Philosophy of Translation - Dangin Al; Dian Natalia Sutanto; Lucia Tri Natalia Sudarmo; Novita Dewi (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2016)
The Philosophy of translation is excluded from the framework of translation studies. Nevertheless, it is actually essential for developing the theory and practice of translation as well as solving both internal and external challenges toward the theory and practice of translation. Hence, this article proposes the inclusion of philosophy in the framework and offers a communicative-functional paradigm as the philosophy of translating from Indonesian into English and vice versa. This paradigm construes translation as intercultural communicative act directed by the target-side purpose. It is rooted ontologically as the recodification of matrix code into target code which results in what Ricoeur calls as the equivalence without identity, epistemologically with the employment of cluster concept and axiologically by directing intercultural mediation with three ethical principles i.e. the primacy of purpose, the loyalty to people and the respecting difference. In Indonesia especially in Yogyakarta, based on the interview conducted to professional translators in PéMad International Translation, this paradigm has been internalized by Indonesian translators without conscious reflection of the paradigm as the philosophical foundation of their translation practices.